2015
DOI: 10.3945/ajcn.114.088534
|View full text |Cite
|
Sign up to set email alerts
|

Moderate weight loss in obese and overweight men preserves bone quality

Abstract: Moderate WL in overweight and obese men did not decrease BMD at any anatomical site or alter cortical and trabecular bone and geometry. Also, despite increased BMD at some sites when maintaining excess body weight, cortical bone showed a trend in the opposite direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
1
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 47 publications
1
22
1
2
Order By: Relevance
“…(15,16) Even voluntary weight loss in the setting of overweight or obesity predicted incident bone loss and fracture at the hip in older women (15) and incident hip bone loss in men. (16) A number of RCTs, most of 6 to 12 months' duration, have examined the effects of weight loss interventions on BMD in overweight or obese older adults (17)(18)(19)(20)(21)(22)(23) In general, the weight loss groups have experienced decreases in body weight of 9% to 10% and decreases in BMD of about 2%. Loss of bone mass in these trials is more consistently shown at the hip than spine.…”
mentioning
confidence: 99%
“…(15,16) Even voluntary weight loss in the setting of overweight or obesity predicted incident bone loss and fracture at the hip in older women (15) and incident hip bone loss in men. (16) A number of RCTs, most of 6 to 12 months' duration, have examined the effects of weight loss interventions on BMD in overweight or obese older adults (17)(18)(19)(20)(21)(22)(23) In general, the weight loss groups have experienced decreases in body weight of 9% to 10% and decreases in BMD of about 2%. Loss of bone mass in these trials is more consistently shown at the hip than spine.…”
mentioning
confidence: 99%
“…While it is appreciated that bone loss occurs throughout the entire lower extremity, the trabecular area above the knee (DF) and below the knee (PT) is a ROI commonly studied because these areas have the highest prevalence of fracture [67], because wheelchair-related accidents are the most common events that make the DF and PT vulnerable to impact and fracture in person with SCI [13,28,33,68]. Although DXA is the most affordable and accessible method to measure BMD at the DF and PT, pQCT is regarded as the more informative and sensitive method.…”
Section: Advanced Bone Imaging: Ct and Mrimentioning
confidence: 99%
“…Three randomized controlled trials (RCT), two with large female study populations (n ≥ 350), were conducted [46, 49, 50], and three intervention studies [47, 48, 51] of which only one recruited men and women [47]. …”
Section: Diet-induced Weight Loss and Vitamin Dmentioning
confidence: 99%
“…A non-randomized intervention study with a small population size of 38 men, followed participants up to 6 months in either a weight loss program or weight maintenance [51]. The weight loss program was designed based on a standard behavior modification nutrition education weight loss program including an individualized caloric intake (500–600 kcal deficit/day) [51].…”
Section: Diet-induced Weight Loss and Vitamin Dmentioning
confidence: 99%
See 1 more Smart Citation